Reading Comprehension in University Students: A Comparative Analysisby Area of Knowledge - Sofía Amavizca Montaño; Erika P. Alvarez-Flores (Universidad Autónoma de Baja California, 2022)
Reading and writing are the working tools of professionals in today's literate communities. This research assesses the reading comprehension (RC) of higher education students about to graduate. The sample was made up of students from various public universities in the state of Sonora (Mexico). An instrument was designed for the express purpose of determining whether there were differences by student discipline or area of knowledge. The analysis employed the SPSS and NVivo programs. The findings show a need to strengthen reading comprehension, and in particular, demonstrate the significant influence of health sciences, where students exhibited higher levels of RC than those in other areas. Generally, it was found that to improve learning, more consideration should be given to reading practices across all education programs.